An overview of cancer thermal therapy technology based on different types of antenna exposure - Kasumawati, Bt Lias; Norlida, Buniyamin; Mohd Zulkarnaen, B Ahmad Narihan (2013)
Cancer thermal therapy is a treatment that uses heat generated using Electromagnetic (EM) fields. This treatment, significantly increase the effectiveness of radiotherapy or chemotherapy treatment towards cancerous tissue or cell. The main goal of this paper is to provide an overview of previous and present technology on cancer thermal therapy which is based on the application of various types of antenna exposure towards cancerous tissue or cell. The paper also proposes a new antenna design that increases the focusing capability and significantly reduces the skin burn effect through the introduction of metamaterial. In addition, the establishment of an antenna with the integration of Electromagnetic Band Gap (EBG) will facilitate depth penetration with selective frequencies. The new antenna design is be expected to significantly improve the specific absorption rate (SAR) distribution